Review of Subcutaneous Wound Drainage in Reducing Surgical Site Infections after Laparotomy. (13th December 2015) - Manzoor, B.; Heywood, N.; Sharma, A.
Abstract : Purpose. Surgical site infections (SSIs) remain a significant problem after laparotomies. The aim of this review was to assess the evidence on the efficacy of subcutaneous wound drainage in reducing SSI. Methods . MEDLINE database was searched. Studies were identified and screened according to criteria to determine their eligibility for meta-analysis. Meta-analysis was performed using the Mantel-Haenszel method and a fixed effects model. Results . Eleven studies were included with two thousand eight hundred and sixty-four patients. One thousand four hundred and fifty patients were in the control group and one thousand four hundred and fourteen patients were in the drain group. Wound drainage in all patients shows no statistically significant benefit in reducing SSI incidence. Use of drainage in high risk patients, contaminated wound types, and obese patients appears beneficial. Conclusion . Using subcutaneous wound drainage after laparotomy in all patients is unnecessary as it does not reduce SSI risk. Similarly, there seems to be no benefit in using it in clean and clean contaminated wounds. However, there may be benefit in using drains in patients who are at high risk, including patients who are obese and/or have contaminated wound types. A well designed trial is needed which examines these factors.